Varieties of Liberalism: Keynesian Responses to the Great Recession in France and Germany. Issue 1 (30th November 2012) - Vail, Mark I.
<x xml:space="preserve">Abstract</x> This article argues that distinctive liberal traditions shaped France and Germany's Keynesian policy responses to the post‐2007 economic crisis. In France, "statist liberalism" privileges an activist state that favors macroeconomic intervention and investment. German "corporate liberalism, " by contrast, is more pluralist and emphasizes the powers and responsibilities of social and economic groups, who are viewed as the fundamental components of the social order. The article argues that these traditions shaped elite interpretations of the crisis and played central roles in defining policy trajectories. They informed a modest French response focused on macroeconomic stimulus that relied on existing income support and a larger German effort centered on a microeconomic strategy of group subsidization. It concludes that these outcomes are inconsistent with traditional institutional accounts and highlights the importance of research on the role of ideas in shaping national responses to economic crises.